THE IMPACT OF BLENDED LEARNING TECHNOLOGIES ON THE DEVELOPMENT OF STUDENTS’ CREATIVE COMPETENCIES IN MUSIC EDUCATION - Zahriddinova Nigina (Ecomind Press, 2026)
This article examines the pedagogical potential of blended learning technologies in the development of students’ creative competencies within music education. The study is grounded in the theoretical principles of competency-based pedagogy, constructivist learning theory, and digital educational environments. It explores how the integration of traditional music instruction with multimedia tools, virtual practice environments, and online collaborative platforms enhances students’ musical thinking, interpretative autonomy, and creative expression. The research is based on a pedagogical experiment conducted in higher and secondary music education settings, comparing traditional teaching approaches with blended learning models. The findings demonstrate that blended learning fosters active engagement, independent learning, and innovative artistic practices, contributing to measurable growth in creative competencies. The study proposes a competency-oriented methodological model for music instruction and highlights pedagogical conditions necessary for the effective implementation of blended learning technologies. The results provide theoretical and practical implications for music educators, curriculum designers, and researchers working in the field of digital and arts education.
Keywords: Blended learning; music education; creative competencies; competency-based education; digital pedagogy; musical thinking; interpretative skills; creative expression; multimedia learning; virtual practice; project-based learning; educational technology; student-centered learning; artistic development; pedagogical innovation.